World Vegetable Soil Competition in 1960-2019 - Syahril, Syahril; Saputra, Arie; Irmayani, Irmayani; Fahlevi, Mirdha; Ertika, Yenni; Mahdani, Said (International Journal of Energy Economics and Policy, 2022)
This study aims to examine the balance and competition of world vegetable oils as a policy formulation to improve palm oil competitiveness in the balance that is partial to the welfare of palm oil farmers in Indonesia.The study used the Vector Error Correction Model (VECM) to analyze short- and long-term balance relationships with the Johansion Cointegration Test. It then analyzed the relationship of bivariate causality with the Pairwise Granger Causality Tests approach. It further analyzes shocks on the values of independent variables that are responded by dependent variables using Impulse Response and Variance Decomposition. The study used monthly data from1960-2019 sourced from the Food and Agriculture Organization (FAO) and the World Trade Organization (WTO). The results of the study proved that the balance in the short-term variable palm oil prices in one and two previous periods was negative to the price of palm oil now. Furthermore, the same findings on soybean oil prices in the previous one and two years negatively affect the price of soybean oil today. Furthermore, the price of coconut oil in the previous two periods also negatively affects the price of coconut oil now. However, the price of coconut oil variable in the previous period had a positive and significant effect on the price of palm oil. While in the long run, the variable price of soybean oil negatively affects the price of palm oil, then the price of coconut oil has a positive effect on palm oil. The results of bivariate causality tests prove that the variable relationship of palm oil prices has a two-way causality with soybean oil prices, then the price of coconut oil (PCO) has a one-way relationship with the price of palm oil (PPO). This means that changes in price of palm oil (PPO) do not affect changes in price of palm oil (PPO), while changes in price of palm oil (PPO) affect changes in price of coconut oil (PCO). Furthermore, the two-way causality relationship between price of coconut oil (PCO) and price of soybean oil (PSO), meaning that changes in price of coconut oil (PCO) will affect price of soybean oil (PSO) and vice versa. Based on the results of impulse response function and variance decomposition explained that the shock of palm oil prices responded to changes in soybean oil prices and coconut oil prices.